Break-in Period ≤24 Hours as an Option for Urgent-start Peritoneal Dialysis in Patients With Diabetes - Hu, Xiaoqing; Yang, Liming; Sun, Zhanshan; Zhang, Xiaoxuan; Zhu, Xueyan; Zhou, Wenhua; Wen, Xi; Liu, Shichen; Cui, Wenpeng (Frontiers in Endocrinology, 2022)
Abstract Background: The optimal break-in period (BI) of urgent-start peritoneal dialysis (USPD) initiation for patients with end-stage renal disease (ESRD) and diabetes is unclear. We aimed to explore the safety and applicability of a BI ≤24 h in patients with ESRD and diabetes. Methods: We used a retrospective cohort design wherein we recruited patients with ESRD and diabetes who underwent USPD at five institutions in China between January 2013 and August 2020. The enrolled patients were grouped according to BI. The primary outcomes were mechanical and infectious complication occurrences, whereas the secondary outcome was technique survival. Results: We enrolled 310 patients with diabetes, of whom 155 and 155 patients were in the BI ≤24 h and BI >24 h groups, respectively. The two groups showed a comparable incidence of infectious and mechanical complications within 6 months after catheter insertion (p>0.05). Logistic regression analysis revealed that a BI ≤24 h was not an independent risk factor for mechanical or infectious complications. Kaplan–Meier estimates showed no statistically significant between-group differences in technique survival rates (p>0.05). Cox multivariate regression analysis revealed that a BI ≤24 h was not an independent risk factor for technique failure. Conclusion: USPD initiation with a BI ≤24 h may be safe and feasible for patients with ESRD and diabetes.